Pemikiran Farid Masudi tentang Sinergi Zakat dan Pajak dalam Mewujudkan Ekonomi Berkeadilan - Muhammad Alwi; Alicia Dos Santos (Prodi Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2025)
Abstract Purpose The purpose of this study is to examine historically Masdar Farid Mas'udi's thoughts on zakat and tax in reducing ‘Double Tax’ to achieve social justice. Method - The research used is a literature study with a research approach that focuses on collecting and analyzing data from written sources, such as books, journals, research reports, official reports, and other references available in libraries or scientific repositories related to the thoughts of Farid Masudi on the synergism of zakat and taxes in a justice economy. Result - Farid Masudi believes that zakat and tax instruments have an important role because both aim to help achieve economic justice. The synergy of zakat and tax to achieve economic justice is applied by several countries, zakat is recognized as a deduction from tax obligations, which means that the amount of zakat paid by zakat payers can be deducted from taxes. This creates a collaboration between zakat and tax to reduce economic inequality. The paradigm of tax that zakat can provide solutions to realize social justice with an innovative approach to ensure taxes are not only a fiscal instrument but a religious and social responsibility. Collaboration between zakat and taxes provides a foundation for distributive justice, where zakat helps the needy, and taxes support the financing of infrastructure and public services needed by the wider community. Masdar's idea of integrating tax and zakat substantially can be a solution to the problem of implementing zakat and tax for Muslims in Indonesia